Ki Demang's Ideological Hegemony Towards The Mojo People Through Folklore and Myth at The Tomb of Mount Kendeng - Lina Nur Anisyah (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
This research shows that the authority of a dominant group that has power can lead to the practice of hegemony in a society. It is like what happened at the tomb of Mount Kendeng in the folklore and myth in the tomb of Mount Kendeng in Mojo hamlet, Wates village, Simo district, Boyolali regency, there is a practice of power hegemony carried out by the leader in Mojo hamlet in the past named Ki Demang. As a person who is considered a Mojo pedestal, all rules and regulations made by Ki Demang as the owner of the authority must be respected and obeyed by the community from the past to the present. For the community, it would be better if the religious tourism objects of Mount Kendeng's tomb were managed by women because it does not rule out the possibility that new ideas can be born that can make the religious tourism object more advanced. Many potential things can actually also be done by women. Local communities must be able to maintain oral traditions that have existed for generations so that these oral traditions are not simply eroded by increasingly modern times. Stakeholders and policies can support the existence of religious tourism objects eating Mount Kendeng by helping to develop and maintain the sustainability of tourism so that it can help improve the local community's economy.